2015
DOI: 10.1016/j.pharep.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of curcumin administration on carbon tetrachloride (CCl4)-induced nephrotoxicity in rats

Abstract: The finding of our study indicates that CUR may have an important role to play in protecting the kidney from oxidative insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 43 publications
10
33
0
1
Order By: Relevance
“…5), aggregations of inflammatory cells and marked inflammatory changes associated with fatty changes (Fig.6), focal necrotic areas, congestion and pyknotic nuclei were also observed (Fig.7). These observations agree with Manjrekar, Jisa, Bag, and Adikary (2008); Morsy et al (2012); Morakinyo, Oludare, Anifowose, and Adegoke (2012); Domitrovic et al (2015);and Hismiogullari et al (2015). Masson trichrome stained sections showed congested thickened portal tract with dense fibrous tissues radiating from the portal vein and extending into the parenchyma (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…5), aggregations of inflammatory cells and marked inflammatory changes associated with fatty changes (Fig.6), focal necrotic areas, congestion and pyknotic nuclei were also observed (Fig.7). These observations agree with Manjrekar, Jisa, Bag, and Adikary (2008); Morsy et al (2012); Morakinyo, Oludare, Anifowose, and Adegoke (2012); Domitrovic et al (2015);and Hismiogullari et al (2015). Masson trichrome stained sections showed congested thickened portal tract with dense fibrous tissues radiating from the portal vein and extending into the parenchyma (Fig.…”
Section: Resultssupporting
confidence: 87%
“…13), severe congestion, vacuolation, inflammatory changes, and dilatation of Bowman's space with glomerular atrophy and periglomerular space (Figs. 14,15,16,and 17), this agree with Manjrekar et al (2008); Morakinyo et al (2012);and Hismiogullari et al (2015). Kidney sections obtained after the two routes of NAC treatment stained with H&E showed improvement in the architecture (Figs.…”
Section: Resultssupporting
confidence: 83%
“…Also, the level of Alb decreased. This result is in coincidence with many other results obtained by different authors who used CCl 4 in their experiments (Hassan et al 2003;Hsiao et al 2003;Hismiogullari et al 2014;Kang andKoppula, 2014 andLu et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The comparative assessment between Group I and Control showed that Curcumin administration decreased oxidative stress by lowering the serum ABTS value. The values obtained validated the antioxidant effect of the tested substance (Curcumin) and are in agreement with previously published results (Gupta et al, 2009;Sharma et al, 2010;Sahin-Kavakli et al, 2011;Savcum et al, 2013;Hussein et al, 2014;Hismiogullari et al, 2014).…”
Section: Discussionsupporting
confidence: 91%